Analisis Tayangan Program Rasis Infotainment Berdasarkan Dimensi Hukum dalam Rangka Pembangunan Negara yang Berkelanjutan - Amelia, Dean Putri; A, Amelia; Riyanto, Rajwa Khaicirinu; Azahra, Nawalia; Salampessy, Fauzan; Rizki, Muhammad; Julius, Tambok; Al Rasyed, Muhammad; Adrini, Shaina Subha (Media Hukum Indonesia (MHI), 2025)
This study aims to analyze three episodes of the Rasis Infotainment program that highlight legal issues, using a Project Based Learning (PjBL) approach and a descriptive qualitative method. The primary focus is to evaluate how well these infotainment broadcasts adhere to journalistic principles and broadcasting ethics in presenting legal content, as well as their contribution to public legal education. Data were collected through direct observation and analyzed using an assessment rubric covering cognitive, affective, conative, sexuality, social norms, and violence dimensions. This limits the potential of infotainment as an effective and ethical medium for legal education. The study recommends improving the quality of legal narratives in infotainment to enhance its strategic role in fostering public legal awareness in the digital era.